Globulart, 1 year ago This isn’t strictly speaking a proof, but it did help me to accept it as it demonstrates the function that makes it 1. 2^3 = 2x2x2 2^2 = 2x2 (2^3)/(2^2) = (2x2x2)/(2x2) = 2 = 2^(3-2) In general terms: (x^a)/(x^b) = x^(a-b) If a and b are the same number this is x^0 and obviously (x^a)/(x^a) is one because anything divided by itself is 1. Hope that helps
This isn’t strictly speaking a proof, but it did help me to accept it as it demonstrates the function that makes it 1.
2^3 = 2x2x2
2^2 = 2x2
(2^3)/(2^2) = (2x2x2)/(2x2) = 2
= 2^(3-2)
In general terms:
(x^a)/(x^b) = x^(a-b)
If a and b are the same number this is x^0 and obviously (x^a)/(x^a) is one because anything divided by itself is 1.
Hope that helps